HERMENEUTIKA MAJELIS HAKIM TERKAIT RATIO DECIDENDI: (Studi Kasus Putusan Nomor 172/Pdt/2019/PT DPS) - Putu Ari Sugiarto Bisma; Deli Bunga Saravistha; Ni Luh Ketut Dewi Yani Putri (Indra Institute Research & Publication, 2023)
Land registration that regulates to ensure land protection is through buying and selling and is registered through buying and selling with a deed drawn up by the Land Deed Official. Illegal land ownership is the use of land by individuals or legal entities to obtain rights or use of land that is not the land, without rights and also illegal use of land. This can lead to land disputes in the community. This study analyzes the ratio decidendi used by the judiciary after studying the important circumstances of the case in terms of proving the transfer of land rights. The interpretation of this study is hermeneutic in nature, interpreted as the process of changing something or a state of ignorance into understanding. In issuing a decision, the judge fulfills the ratio decidendi criteria based on the court decision. It must contain the reasons and justification for the decision. It must also contain certain articles of statutory regulations. The Panel of Judges must understand the law in accordance with what has been given by the parties during the trial. If the plaintiff can prove his lawsuit, the judge will accept the lawsuit, but on the contrary if the plaintiff cannot prove his claim and the defendant can prove that he is against the plaintiff's claim, the judge will reject the plaintiff's lawsuit.